'Stick with your own kind, or hang with the locals?' Implications of shoaling strategy for tropical reef fish on a range‐expansion frontline. (15th January 2018) - Smith, Shannen M.; Fox, Rebecca J.; Booth, David J.; Donelson, Jennifer M.
Abstract: Range shifts of tropical marine species to temperate latitudes are predicted to increase as a consequence of climate change. To date, the research focus on climate‐mediated range shifts has been predominately dealt with the physiological capacity of tropical species to cope with the thermal challenges imposed by temperate latitudes. Behavioural traits of individuals in the novel temperate environment have not previously been investigated, however, they are also likely to play a key role in determining the establishment success of individual species at the range‐expansion forefront. The aim of this study was to investigate the effect of shoaling strategy on the performance of juvenile tropical reef fishes that recruit annually to temperate waters off the south east coast of Australia. Specifically, we compared body‐size distributions and the seasonal decline in abundance through time of juvenile tropical fishes that shoaled with native temperate species ('mixed' shoals) to those that shoaled only with conspecifics (as would be the case in their tropical range). We found that shoaling with temperate native species benefitted juvenile tropical reef fishes, with individuals in 'mixed' shoals attaining larger body‐sizes over the season than those in 'tropical‐only' shoals. This benefit in terms of population body‐size distributions was accompanied by greater social cohesion of 'mixed' shoals across the season. Our results highlight the impact that sociality and behavioural plasticity are likely to play in determining the impact on native fish communities of climate‐induced range expansion of coral reef fishes. Abstract : Successful climate‐mediated range shifts are likely to be influenced by the behaviour of individuals in the range expansion front line, however the importance of invader phenotype is currently poorly understood. Behavioural observations of tropical fish recruits, across one season in a novel temperate environment, show that shoaling with resident temperate fish may provide fitness benefits for these tropical invaders in terms of increased body size and greater social cohesiveness. Although thermal physiological constraints currently limit expansion success in the temperate region, it is likely that benefits derived from shoaling strategy will influence individual survival in the future as warming continues.